Analisis Pengaruh Gaya Belajar Manager dan Gaya Kepemimpinan terhadap Keefektifan Organisasi dengan Kinerja Pegawai sebagai Variabel Intervening (Studi pada PT. UPGRI) - Aminingtyas, Septi Andini; Indarto, Indarto; Albert, Albert (Universitas PGRI Semarang, 2025)
Every employee needs a manager's learning style and a leader's leadership style that can improve employee performance, because with high employee performance, employee performance becomes more focused and organizational goals can be achieved more quickly. This study aims to determine the effect of learning style and leadership style on organizational effectiveness with employee performance as an intervening variable. The type of research used is explanatory research, with a quantitative approach. The sampling technique used is proportionate stratified random sampling, with the determination of the number of samples using the Slovin formula and the number of samples obtained was 78 employees. Data sources were obtained from primary data by distributing questionnaires and secondary data with documentation. This study uses path analysis with the help of SPSS 25.0 software. The results of this study indicate that Manager Learning Style and Leadership Style have a significant effect on Organizational Effectiveness and Employee Performance. Organizational Effectiveness mediates Manager Learning Style and Leadership Style on Employee Performance. The most dominant variable in influencing Organizational Effectiveness and Employee Performance needs to be considered. The variable is Manager Learning Style, with Manager Learning Style, employees feel more motivated and their performance increases.